Fracture mechanics and its application to wood / Mustafa Mohamad - Mohamad, Mustafa (1998)
Using fracture mechanics one can predict the strength of wood that contains knots, notches, cracks and other discontinuities. The author undertakes to introduce the reader the fundamentals of fracture mechanics and its application to wood incorporating a small-scale experiment using the standard test procedures (BS 5447S 1977)* It is a commonly held belief that the isotropic solution can also give satisfactory results for most orthotropic materials. For isotropic materials there are three fracture values in respect to the three modes of crack propagation. But, for wood that is modelled as an orthotropic materials, six different fracture toughness values exist for every one of the three modes. Two standard types of test piece that are currently re-commended in the BS 5447s 1977 were used (i.e. SEN bend and CTS test piece). The species of wood used was Keruing. For the purpose of the study, specimen were cut so that it consists of crack parallel and perpendicular to grain. Test results show an agreeable KIc value for crack parallel to grain from the GTS test piece. The value obtained was O.56 MN *3/2 i.e. within the range of 0.5 - 1 MN m-3/2